Community-based intervention in reducing flood impacts in Gambia. Issue 1 (March 2021) - Jonga, A; Meilianda, E; Nizamuddin,
Abstract: Flood has caused significant damage to the agricultural sector, which results in low productivity and causes famine in Kaba-kama community of Basse in the Upper river region of the Gambia. This study analyses the potential role of the community's mitigation efforts to reduce the flood impact in the Gambia. The objective is to determine the influence of community-based intervention activities in reducing the flood impact at the community level. The primary data are obtained in this study from own previous experience by participating in the community work ("Te-setto") to mitigate the impact of flood, and interviews in a form of questionnaires to the members of the VDC in Kaba-kama community. Literature reviews from journals, books, and the final report about the disaster in 2018 by NDMA has served as a secondary source of data for the study. Notifiable, the community-based organization (Village Development Committee -VDC), is the key pioneer of the initiative. This study exemplifies the successful collective efforts by the communities and government in different regions and the country at large in practicing flood adaptive and mitigation strategies, which has potential to be implemented elsewhere in other famine-prone countries in the world.